Modeling complex crack paths in ceramic laminates: A novel variational framework combining the phase field method of fracture and the cohesive zone model. Issue 8 (July 2018) - Carollo, V.; Reinoso, J.; Paggi, M.
Abstract: The competition between crack penetration in the layers and cohesive delamination along interfaces is herein investigated in reference to laminate ceramics, with special attention to the occurrence of crack deflection and crack branching. These phenomena are simulated according to a recent variational approach coupling the phase field model for brittle fracture in the laminae and the cohesive zone model for quasi-brittle interfaces. It is shown that the proposed variational approach is particularly suitable for the prediction of complex crack paths involving crack branching, crack deflection and cohesive delamination. The effect of different interface properties on the predicted crack path tortuosity is investigated and the ability of the method to simulate fracture in layered ceramics is proven in relation to experimental data taken from the literature.